The main issues of the Cyrene necropolis and the use of remote sensing for monitoring in the case of the eastern necropolis. (7th November 2016) - Al Raeid, Fawzi; Di Valerio, Eugenio; Di Antonio, Maria Giorgia; Menozzi, Oliva; Abdalgader El Mziene, Mazen A. S.; Tamburrino, Clara
Abstract: Cyrene offers one of the largest and most spectacular necropoleis of the Mediterranean basin and, owing especially to its vastness, it is particularly difficult to control and protect. It reveals an extraordinary patrimony of rock-cut architecture, monumentally built around the ancient site, and also represents a zone at major risk of damage and destruction as a result of continuous looting, uncontrolled urbanisation and vandalism. Recent studies by Jim and Dorothy Thorn have presented a preliminary view and gazetteer of the architectonic monumentality, especially of the rocky chamber tombs, showing the need for survey projects in the area. A joint team of Libyan and Italian archaeologists, geologists, topographers and technicians of the local Department of Antiquities and Chieti University started in 1999 a project of surveying and mapping the southern and eastern parts of the necropolis, giving birth to a GIS using differential GPS and Robotic total station for the positioning and recording of the tombs, as well as multispectral HD satellite images, previously orthorectified and georeferred, combined with old maps and RADAR data for a highly detailed topographic base, up to DEM and DTM. From 2004, the survey and the GIS have been extended to the western and northern parts of the necropolis, at the moment counting more than 2, 000 mapped and recorded tombs. An important step in the last two years has been the use of remote-sensing and photo-interpretation analysis in order to map the damages of urbanisation and modern construction in the areas of the necropolis. Using images covering the development of the situation every two to three months, mainly shots coming from Google Earth archives, in combination with further satellite images specifically bought for a more complete view of the last two to three years, it has been possible to start drawing a map of the areas under threat from building works and urbanisation. The aim of this paper is to present the main problems of this huge necropolis, which is at the moment one of the most threatened areas of Cyrene, every day at risk from the destruction of its monumental buildings. Abstract : تقدم القيروان واحدة من أكبر وأعظم المقابر في حوض البحر الأبيض المتوسط والتي نظرً لمساحتها الكبيرة كان من الصعب السيطرة عليها وحمايتها. إن هذه المقابر تكشف عن إرث معماري منحوت بالصخر ومبني بشكل ضخم وعظيم حول الموقع القديم، كما تمثل منطقة معرضة للتخريب والهدم نتيجة السرقات المستمرة والامتداد العمراني غير المسيطر عليه والتخريب المتعمد. إن الدراسات الحديثة التي قام بها جيم ودوروثي ثورن قد قدمت نظرة مبدئية وفهرساً جغرافياً للأثر المعماري، وخاصة لغرف المقابر الصخرية، مما يظهر الحاجة لمشاريع مسحية للمنطقة. لقد بدأ فريق مشترك من علماء الآثار الطليان والليبيين والجيولوجيين والمساحين والفنيين من دائرة الآثار وجامعة كيتي في عام 1999 مشروعاً لمسح ورسم خرائط الجزء الجنوبي والشرقي للمقابر،مما ولّد نظام معلومات جغرافية باستخدام نظام تحديد المواقع التفاضلي وجهاز المحطة المتكاملة لموضعة وتسجيل المقابر، بالإضافة إلى صور الأقمار الصناعية عالية الدقة متعددة الأطياف، التي تم تصحيحها بالسابق وإرجاعها إلى موقعها الجغرافي، وذلك بالجمع بين خرائط قديمة وبيانات رادارية من أجل الحصول على قاعدة طوبوغرافية عالية التفصيل ونموذج الارتفاع الرقمي ونموذج التضاريس الرقمي . وقد تمت توسعة رقعة المسح ونظم المعلومات الجغرافية منذ عام 2004 ليصل إلى غرب وشمال المقابر، مما يمثل حالياً أكثر من 2000 قبر قد تم رسم خرائطها وتسجيلها. إن الخطوة المهمة التي تم القيام بها آخر عامين هي استخدام الاستشعار عن بعد وتفسير الصور وتحليلها من أجل رسم خرائط للخسائر التي حصلت نتيجة الزحف العمراني والبناء الجديد في مناطق المقابر. إن استخدام اللقطات التي تغطي تطوير الموقع كل شهرين أو ثلاثة أشهر، بالغالب الصور من أرشيف جوجل الأرض، بالإضافة إلى صور فضائية أخرى تم شراؤها لتكوين مشهد أكثر اكتمالاً للسنتين أو الثلاثة السابقة، قد جعل البدء برسم خريطة للمناطق المهددة من أعمال البناء والزحف العمراني ممكناً. إن هدف هذه الورقة هو تقديم أهم المشاكل التي تعاني منها هذه المقابر الضخمة، وهي حالياً واحدة من أكثر المناطق عرضة للتهديد في القيروان حيث تتعرض بشكل يومي لخطر هدم مبانيها العظيمة.